STRATEGI PEMASARAN PERUSAHAAN DALAM MEMPERTAHANKAN PENJUALAN PADA BISNIS BAKERY LOT.BUTTER - Fadiyah Zahra; Iwan Sukoco; Cecep Safa’atul Barkah (JURNAL LENTERA BISNIS, 2024)
Lot.butter, a bakery business founded in Bandung in 2021, has succeeded in attracting attention with its quality products, especially Daifuku which went viral in 2023 thanks to reviews from famous Instagram celebrities. The popularity and sales of Lot.butter have increased significantly, in contrast to the trend of artist cake businesses in 2017 which did not last long because they only relied on popularity without the support of business skills. To avoid a similar fate, Lot.butter plans a mature marketing strategy to maintain sales. This research uses qualitative methods with IFE, EFE, IE, SWOT and QSPM analysis, as well as data collection techniques through interviews with 7 informants and documentation studies. As a result, marketing strategies through various social media platforms such as Tiktok, Facebook, Twitter and YouTube, exclusive promotions with online delivery partners, as well as expansion into the Jakarta bakery market are recommended.